Study of beauty hadron decays into pairs of charm hadrons - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physical review letters, 2014)
First observations of the decays Λ0b→Λ+cD−(s) are reported using data corresponding to an integrated luminosity of 3 fb−1 collected at 7 and 8 TeV center-of-mass energies in proton-proton collisions with the LHCb detector. In addition, the most precise measurement of the branching fraction B(B0s→D+D−s) is made and a search is performed for the decays B0(s)→Λ+cΛ−c. The results obtained are B(Λ0b→Λ+cD−)/B(Λ0b→Λ+cD−s)=0.042±0.003(stat)±0.003(syst),[B(Λ0b→Λ+cD−s)B(¯B0→D+D−s)]/[B(Λ0b→Λ+cπ−)B(¯B0→D+π−)]=0.96±0.02(stat)±0.06(syst),B(B0s→D+D−s)/B(¯B0→D+D−s)=0.038±0.004(stat)±0.003(syst),B(¯B0→Λ+cΛ−c)/B(¯B0→D+D−s)<0.0022[95% C.L.],B(B0s→Λ+cΛ−c)/B(B0s→D+D−s)<0.30[95% C.L.].Measurement of the mass of the Λ0b baryon relative to the ¯B0 meson gives M(Λ0b)−M(¯B0)=339.72±0.24(stat)±0.18(syst) MeV/c2. This result provides the most precise measurement of the mass of the Λ0b baryon to date.
Gesehen am 28.08.2020